Gondolatok a magyar „Rövid 20. század” történetének nemzeti-polgári-konzervatív szintéziséről. - Gulyás, László (Közép-Európai Közlemények, 2023)
Our study, we outline the logical along which national-bourgeois-conservativa historians should write the syntehesis of Hungarian „short history 20th century”. We make a proposal on where to develop the focal points of theit own synthesis.